DESAIN SARINGAN PASIR LAMBAT - Utomo, Sudiyo; Sir, Tri M. W.; Sonbay, Albert (Jurnal Teknik Sipil, 2012)
Kolhua IPAB is a means of channeling water to the people and surrounding villages Kolhua, however IPAB has a major problem is turbidity. Slow sand filtration (SPL) is a technique used to improve water quality. Runoff and water quality modeling is obtained by making use of PVC pipe 6 ". Flow rate shall be in accordance with SNI 03.3981.2008 and the resulting water quality after filtration should be below the standard of Minister Regulation. 492 in 2010. Based on the results of research with the discharge of springs Kolhua 0.015 m3/second, SPL design thickness of 60 cm of sand obtained by the speed of 0.22 m/h at head 0.15 m and capacity area of the tub filtering is 245 m2 with dimensions of 11 x 22 m, to the thickness of the sand 80 cm is obtained velocity 0.32 m/h at head 0.25 m and capacity area of the tub filtering is 169 m2 with dimensions of 10 x 20 m, to a thickness of 100 cm of sand obtained by the speed of 0.33 m/h at head 0.30 m and capacity area of the tub filtering is 164 m2 with dimensions of 9 x 18m.